Progress Toward Restoring the Everglades: The Sixth Biennial Review - 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Everglades ecosystem is vast, stretching more than 200 miles from Orlando to Florida Bay, and Everglades National Park is but a part located at the southern end. During the 19th and 20th centuries, the historical Everglades has been reduced to half of its original size, and what remains is not the pristine ecosystem many image it to be, but one that has been highly engineered and otherwise heavily influenced, and is intensely managed by humans. Rather than slowly flowing southward in a broad river of grass, water moves through a maze of canals, levees, pump stations, and hydraulic control structures, and a substantial fraction is diverted from the natural system to meet water supply and flood control needs. The water that remains is polluted by phosphorus and other contaminants originating from agriculture and other human activities. Many components of the natural system are highly degraded and continue to degrade.
Keywords: Environment and Environmental Studies; Earth Sciences

Progress Toward Restoring the Everglades: The Seventh Biennial Review - 2018 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure that was intended to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. Over the past two years, impressive progress has been made in planning new CERP projects, and the vision for CERP water storage is now becoming clear. Construction and completion of authorized CERP projects will likely take several decades, and at this pace of restoration, it is even more imperative that agencies anticipate and design for the Everglades of the future. This seventh biennial review assesses the progress made in meeting the goals of the CERP and provides an in-depth review of CERP monitoring, with particular emphasis on project-level monitoring and assessment. It reviews developments in research and assessment that inform restoration decision making, and identifies issues for in-depth evaluation considering new CERP program developments, policy initiatives, or improvements in scientific knowledge that have implications for restoration progress.
Keywords: Environment and Environmental Studies; Earth Sciences

Re-Engineering Water Storage in the Everglades: Risks and Opportunities - National Research Council (The National Academies Press, 2005)
The Water Science and Technology Board and the Board on Environmental Studies and Toxicology have released the seventh and final report of the Committee on Restoration of the Greater Everglades Ecosystem, which provides consensus advice to the South Florida Ecosystem Restoration Task Force on various scientific and technical topics. Human settlements and flood-control structures have significantly reduced the Everglades, which once encompassed over three million acres of slow-moving water enriched by a diverse biota. To remedy the degradation of the Everglades, a comprehensive Everglades Restoration Plan was formulated in 1999 with the goal of restoring the original hydrologic conditions of its remaining natural ecosystem. A major feature of this plan is providing enough storage capacity to meet human needs while also providing the needs of the greater Everglades ecosystem. This report reviews and evaluates not only storage options included in the Restoration Plan but also other options not considered in the Plan. Along with providing hydrologic and ecological analyses of the size, location and functioning of water storage components, the report also discusses and makes recommendations on related critical factors, such as timing of land acquisition, intermediate states of restoration, and tradeoffs among competing goals and ecosystem objectives.
Keywords: Earth Sciences; Environment and Environmental Studies

Progress Toward Restoring the Everglades: The Second Biennial Review - 2008 - National Research Council (The National Academies Press, 2008)
This book is the second biennial evaluation of progress being made in the Comprehensive Everglades Restoration Plan (CERP), a multibillion-dollar effort to restore historical water flows to the Everglades and return the ecosystem closer to its natural state. Launched in 2000 by the U.S. Army Corps of Engineers and the South Florida Water Management District, CERP is a multiorganization planning process that includes approximately 50 major projects to be completed over the next several decades.
Keywords: Environment and Environmental Studies; Earth Sciences